Wireless Measurement of Sympathetic Arousal During in vivo Occupational Therapy Sessions - Hedman, Elliot; Schoen, Sarah A.; Miller, Lucy J.; Picard, Rosalind (Frontiers in Integrative Neuroscience, 2020)
PURPOSE: One goal of occupational therapists working with children who have sensory processing challenges is the regulation of arousal. Regulation strategies have not been evaluated using an empirical measure of physiological arousal. OBJECTIVE. To establish the feasibility of using an objective physiologic measure of sympathetic arousal in therapeutic settings and explore the relation between therapeutic activities and sympathetic arousal. To evaluate changes in electrodermal activity (EDA) during occupational therapy sessions. METHOD. Twenty-two children identified with Sensory Modulation Dysfunction (SMD) wore a wireless EDA sensor during 50-minute occupational therapy sessions (n = 77 sessions). RESULTS. All children were able to wear the sensor on the lower calf without being distracted by the device. The five insights below are based on a comparison of EDA recordings in relation to therapists’ reflections describing how sympathetic arousal might correspond to therapeutic activities. CONCLUSION. Objective physiological assessment of a child’s sympathetic arousal during therapy is possible using a wireless EDA measurement system. Changes in EDA may correspond directly with therapeutic activities. The paper provides a foundation for designing future therapeutic studies that include continuous measures of EDA.